Penentuan Mahar Berdasarkan Tingkat Pendidikan Pengantin Perempuan Perspektif Hukum Adat dan Hukum Islam - Ridwan, Muhammad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2022)
The determination of the dowry in the Purba Baru was carried out from generation to generation, so it was difficult to shift it, even though the times had progressed. Uniquely, the determination of dowry in Purba Baru is based on the education level of the bride, even though in Islam it is stated that the form of dowry is only that which is valuable and useful. This research is qualitative, which prioritizes quality requirements in the form of understanding the problem. While the informants in this study were four people, namely 1) community leaders 2) youth 3) women 4) community. The techniques used to collect data in the consensus of this study were 1) interviews 2) observation 3) and 3) documentation. Determining the dowry based on the level of education in Purba Baru is an act that creates two legal consequences if the purpose of the determination is to elevate the dignity of women, especially regarding whether an action is legal or not, it causes things that are contrary to the Shari'a thus it becomes illegal to accept it, even may become unlawful.